In situ reconstruction with autologous graft in the treatment of secondary aortoenteric fistulas: A retrospective case series. (January 2020) - Feo, Claudio F.; Ginesu, Giorgio C.; Pinna, Antonio; Galotti, Francesca; Paliogiannis, Panagiotis; Fancellu, Alessando; Porcu, Alberto
Abstract: Infections caused by secondary aortoenteric fistulas (SAEF) may be extremely complex and threaten patient's life. We report our surgical approach to SAEF consisting in removal of the infected graft and in situ reconstruction using an autologous venous graft. Seven consecutive patients with SAEF treated with graft removal and in situ reconstruction using an autologous venous graft from 2008 to 2017 were reviewed. Six of seven patients (86%) survived 30-day. In one case a graft thrombosis and acute lower limb ischemia occurred requiring re-operations. All patients received injective antibiotic therapy for 20 days, followed by oral therapy for 3 months. There were no major complications at long-term follow-up. Our results suggest that superficial femoral vein reconstruction of the abdominal aorta for SAEF is effective with an acceptable in-hospital mortality and low rate of major complications. We stress the importance of the deep femoral veins to create the graft because the large saphenous vein is often affected by significant intimal hyperplasia that can cause steno-occlusive complications. Highlights: In situ reconstruction for secondary aortoenteric fistulas is effective. We stress the importance of the deep femoral veins to create the graft. One of the largest series of secondary aortoenteric fistulas treated with venous graft. Morbidity and mortality are acceptable at long-term follow-up.